Kolaborasi dalam Skenario Pelembagaan Sosial (SPS) atau Social Institution Scenario (SIS) Permukiman Sempadan Sungai - Muhammad Agus Syukron; Wahyudi Wahyudi (Journal on Education, 2022)
Environmental experts and social experts have a dilemmatic view of responding to communities inhabiting river border settlements, that the risk of degradation land resources, disasters and safety to river border settlers, in others has an optimistic view that increasing the capacity and proficiency of land resources will bring the community closer to environmental functions and services, so that it will be able to increase the level of community welfare. This study examines the process of structuring the social interaction of community elements residing on the border of the Brantas River "Kampung Wisata Warna-Warni" Jodipan Village, Malang City. This study applies a qualitative approach to understand the main problems of collaboration in the preparation of social institutional scenarios through document studies, observations, interviews and Focus Group Discussions. (FGD). The research produced an overview, namely: 1) The location of the settlement of Kampung Wisata Warna-Warni Jodipan Village has access to a very strategic location in the city center; 2). The interference of stakeholders outside the community of Kampung Wisata Warna-Warni Jodipan has a significant effect in changing people's social habits and behavior; and 3). Stakeholder collaboration in the scenario of social institutionalization of the settlement of Kampung Wisata Warna-Warni Kelurahan Jodipan Malang city through the engineering of the 7C Lyon concept is very relevant.